Higher Education Information System / Suresh Kannan Subramanian - Suresh Kannan, Subramanian (2000)
Web based Higher Learning Education Information System is an information system developed to inform dissemination and retrieval of universities and colleges information online. This application makes fully use of web technology which enables users to access to the internet from their dekstops. Thus, making this system accessible by wider group of users compared to the local area network system application. Beside that, a web search engine also developed as extended function to enable web searching.this project starts with a report in chapter one by looking into the project background, defining the project objective, motivation and scope. Chapter two concerns on the feasible study for this project. It will discuss about existing higher education systems in the internet. Chapter three covers the analysis part of this project. Methodology, functional requirements and all the system requirements will be discussed here. Chapter four discusses beginning design of this project. It will cover the design principles, process design and charts.